Intervenções educativas com usuários de medicamentos como estratégias terapêuticas - dos Reis Sarra, Josiane [UNESP]; Pella Legramandi, Victor Hugo [UNESP]; Silva Sacramento, Luis Vitor [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2013)
A review and analysis of the literature on educative interventions (EI) for medicine users was carried out. For this purpose, databases were searched by employing descriptors related to pharmaceutical care, education and health, covering the period from 1997 to early 2011. A set of 21 articles related to EI with medicine users were selected, 18 (85.7%) of which referred to studies on basic health care. The EI most commonly reported in the articles were: talks, group discussions and educative material. The positive outcomes reported were: improvement in quality of life (better acceptance of the disease), economic advantages (reduction in number of medical consultations) and clinical improvement (risk reduction, prevention of complications).

Foi realizada uma revisão e análise da literatura sobre intervenções educativas (IE) com usuários de medicamentos. Para isso, foram consultadas bases de dados empregando-se descritores relacionados à educação, saúde e cuidado farmacêutico, no período de 1997 a 28/02/2011. Foram selecionados 21 artigos relacionados à IE com usuários de medicamentos, sendo que 18 (85,7%) deles referiam-se a trabalhos desenvolvidos na atenção básica a saúde. As IE mais comumente relatadas nos artigos selecionados foram: palestras, grupos de discussões e material educativo. Como resultados positivos foram relatados: melhora da qualidade de vida(melhor aceitação da doença), vantagens econômicas (redução de retornos e consultas), melhora clínica (redução dos riscos, prevenção de complicações). Palavras-chave: Educação em Saúde. Atenção Farmacêutica. Saúde da Família
Educational interventions among medicine users as a therapeutic strategy
Keywords: Family Health; Health Education; Pharmaceutical Care; drug use; economic aspect; health education; human; medical literature; pharmaceutical care; quality of life